121 Bioinformatic imaging and molecular investigation for a role of p22phox C242T polymorphism in inhibiting endothelial ROS production. (16th May 2012) - Meijles, D N; Howlin, B J; Li, J-M
Abstract : The p22 phox is a key component of the cytochrome b558 of the NADPH oxidase (Nox), which by generating reactive oxygen species (ROS) is involved in the pathogenesis of many cardiovascular diseases. Several clinical studies have reported that a single nucleotide polymorphism (SNP) of p22 phox (C242T) is negatively associated with the incidence of coronary heart disease. However, the mechanism involved remains unknown. In this study we combined computer molecular modelling with cell and molecular biology to investigate the potential mechanism of the p22 phox C242T on endothelial ROS production. Our in silico 3D protein structure model of p22 phox consists of an N-terminal transmembrane domain (124 a.a.) and a C-terminal cytoplasmic domain (71 a.a.). The p22 phox C242T causes a substitution of His72 to Tyr72 in its extracellular loop, which results in significant morphological changes in the putative interactive region of the p22 phox with the catalytic subunit (Nox2), and this may result in a reduced ROS production. To test this hypothesis, we generated p22 phox C242T construct by site-directed mutagenesis and transfected mouse microvascular endothelial cells (SVEC4-10) with either wild-type (WT) p22 phox or p22 phox C242T. Compared to WT control, C242T had no significant effect on basal ROS production. However, when cells were stimulated with TNFα (100 U/ml, 45 min), C242T significantly reduced (48%±5.6%) the levels of ROS production detected by both lucigenin-chemiluminescence and DCF fluorescence. Reduced ROS production was accompanied with inhibition in TNFα-induced ERK1/2 and p38MAPK activation and NFκB phosphorylation. Furthermore, we found that C242T reduced significantly (31.9%±2%) the TNFα (12 h)-induced endothelial cell apoptosis as detected by Annexin V flow cytometry. In conclusion, we reported for the first time that the p22 phox C242T SNP is associated with a significant protein morphological change, which affects the activity of NADPH oxidase, and reduces the ROS production by endothelial cells when challenged by TNFα. Our study provides important insight into the mechanism of p22 phox C242T SNP and its clinical relevance as a natural inhibitory factor of the incidence of coronary heart disease (CHD).